(untitled) (CIPEEX, 2025)
This study examines the tension between the sovereignty of jury verdicts and criminal review after final judgment, under article 621 of the Brazilian Code of Criminal Procedure. It is a bibliographic and case-law analysis that systematizes doctrine and higher-court precedents to set admissibility criteria and limits on review over jury decisions. The aim is to delineate, from the standpoint of legal certainty, when review may result in acquittal, annulment of the trial, reclassification, or sentence modification without undermining the jurors’ sovereign will. The method consisted of a critical reading of items I–III of article 621, focusing on decisions contrary to the record, convictions grounded on falsified elements, and new, reliable evidence. The findings reveal two approaches to reconciliation: (i) requiring a new jury trial when review is granted; and (ii) allowing direct acquittal to prevent unjust decisions from persisting. It concludes that sovereignty is not absolute and exceptionally yields to manifest factual or legal error and supervening evidence, with criminal review operating as a safeguard of substantive justice.